2010
DOI: 10.1007/s11270-010-0636-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Phosphorus Mobility and Bioavailability in the Hyporheic Zone of a Chalk Stream

Abstract: This paper investigates the changes in bioavailable phosphorus (P) within the hyporheic zone of a groundwater-dominated chalk stream. In this study, tangential flow fractionation is used to investigate P associations with different size fractions in the hyporheic zone, groundwater and surface water. P speciation is similar for the river and the chalk aquifer beneath the hyporheic zone, with 'dissolved' P (<10 kDa) accounting for~90% of the P in the river and >90% in the deep groundwaters. Within the hyporheic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Similarly the complexities of phosphate sources (Holman et al, 2010) and mobility (Lapworth et al, 2011;Mellander et al, 2013) have been outside the scope of this study.…”
Section: Applicability Of the Results To Other Catchmentsmentioning
confidence: 98%
“…Similarly the complexities of phosphate sources (Holman et al, 2010) and mobility (Lapworth et al, 2011;Mellander et al, 2013) have been outside the scope of this study.…”
Section: Applicability Of the Results To Other Catchmentsmentioning
confidence: 98%
“…A number of studies have found that natural attenuation at the groundwater-surface water interface is a significant control on observed river nitrate concentrations (Allen et al, 2010;Lapworth et al, 2011;Pretty et al, 2006;Smith et al, 2009). Lapworth et al (2011) showed that ecologically significant P concentrations (20-30 μg/L) are present in the hyporheic zone in dissolved and colloidal forms.…”
Section: Nitrogen Fate and Transport In Groundwatermentioning
confidence: 99%
“…Lapworth et al (2011) showed that ecologically significant P concentrations (20-30 μg/L) are present in the hyporheic zone in dissolved and colloidal forms.…”
Section: Nitrogen Fate and Transport In Groundwatermentioning
confidence: 99%
See 2 more Smart Citations